2021
DOI: 10.1098/rsta.2019.0624
|View full text |Cite
|
Sign up to set email alerts
|

An econometric model for intraday electricity trading

Abstract: This paper develops an econometric price model with fundamental impacts for intraday electricity markets of 15-min contracts. A unique dataset of intradaily updated forecasts of renewable power generation is analysed. We use a threshold regression model to examine how 15-min intraday trading depends on the slope of the merit order curve. Our estimation results reveal strong evidence of mean reversion in the price formation mechanism of 15-min contracts. Additionally, prices of neighbouring contracts exhibit st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…What is more, the price fluctuations during the final trading hour of contract h are correlated with the fluctuations during the final trading hour of the previously expired contract h − 1. This observation is in line with [20,21], who found similar results for the prices and price changes of 15-min contracts. Figure 6 illustrates these correlations for the measure VSD.…”
Section: Forecast Indicatorssupporting
confidence: 91%
See 3 more Smart Citations
“…What is more, the price fluctuations during the final trading hour of contract h are correlated with the fluctuations during the final trading hour of the previously expired contract h − 1. This observation is in line with [20,21], who found similar results for the prices and price changes of 15-min contracts. Figure 6 illustrates these correlations for the measure VSD.…”
Section: Forecast Indicatorssupporting
confidence: 91%
“…Besides external drivers, we showed that characteristics of the (cross-sectional) time series of contracts can be used as forecasting variables. This complements the findings of [20,21], who found a similar correlation for 15-min contracts on prices. Because of (auto-)correlations, realized price fluctuations of previously expired contracts as well as fluctuations during the elapsed trading time of the contract itself have an explanatory power for price fluctuations during the (final) peak trading hour.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Limited access to high-quality high-frequency trading data, however, has so far somewhat hindered research on new models for intra-day trading, and few models have so far been proposed in the literature. Kremer et al [9] consider a novel and extensive dataset which contains high-frequency electricity price transaction data for 15 min contracts from the German market and linked fundamental supply and demand data. What is more, it includes the same intra-daily updated forecasts of wind and solar power generation available to traders on the intraday market.…”
mentioning
confidence: 99%